Impacts of tidal flat reclamation on suspended sediment dynamics in the tidal-dominated Wenzhou Coast, China - Zhang, Rong; Chen, Yongping; Chen, Peixiong; Zhou, Xin; Wu, Biying; Chen, Kehao; Sun, Zhilin; Yao, Peng (Frontiers in Marine Science, 2023)
Reclamation of tidal flats is one of the engineering measures of expanding land area and developing the economy in coastal areas; however, this process disturbs the natural processes of the tidal flat system. Taking the flood-tidal dominant Oufei tidal flat at the Wenzhou coast as a study area, the influences of tidal flat reclamation on tidal and suspended sediment dynamics were comprehensively investigated via numerical modeling. Before the reclamation, the Eulerian residual current flows alongshore and the residual sediment transport on-shore in the tidal flat area. The reclamation reduces the tidal flat area, shifting the M4 co-phase line toward the coast and squeezing the flood-dominated area. Consequently, the tidal current is weakened and the suspended sediment concentration (SSC) is reduced, but the residual sediment transport change insignificantly. The residual sediment transport in the Feiyunjiang Estuary is controlled by the tidal pumping effect. The upper estuary shows a net sediment transport landward, while a seaward transport is observed in the lower estuary, which further splits into two circulation outside the estuary. The south Oufei dike construction interferes the northern sediment circulation, resulting in the alteration of local SSC and enhancing landward sediment transport inside the estuary. The methodology and understandings arising from this study could be a good reference for the analysis of suspended sediment transport under tidal flat reclamation effects at other sites.